The emerging roles of LINC00511 in breast cancer development and therapy - Zhao, Lifeng; Biswas, Sangita; Li, Yepeng; Sooranna, Suren Rao (Frontiers in Oncology, 2024)
Breast cancer (BC) is associated with malignant tumors in women worldwide with persistently high incidence and mortality rates. The traditional therapies including surgery, chemotherapy, radiotherapy and targeted therapy have certain therapeutic effects on BC patients, but acquired drug resistance can lead to tumor recurrence and metastasis.This remains a clinical challenge that is difficult to solve during treatment.Therefore, continued research is needed to identify effective targets and treatment methods, to ultimately implement personalized treatment strategies. Several studies have implicated that the long non-coding RNA LINC00511 is closely linked to the occurrence, development and drug resistance of BC. Here we will review the structure and the mechanisms of action of lnc RNA LINC00511 in various cancers, and then explore its expression and its related regulatory mechanisms during BC. In addition, we will discuss the biological functions and the potential clinical applications of LINC00511 in BC.